2017
DOI: 10.3168/jds.2016-11536
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Interaction of the isomers carvacrol and thymol with the antibiotics doxycycline and tilmicosin: In vitro effects against pathogenic bacteria commonly found in the respiratory tract of calves

Abstract: Bovine respiratory disease is the major problem faced by cattle, specially calves, leading to reduced animal performance and increased mortality, consequently causing important economic losses. Hence, calves must be submitted to antibiotic therapy to counteract this infection usually initiated by the combination of environmental stress factors and viral infection, altering the animal's defense mechanism, and thus allowing lung colonization by the opportunistic bacteria Mannheimia haemolytica and Pasteurella mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…This compound has previously been reported to confer antimicrobial activity against bovine respiratory pathogens (Kissels et al . ), and likely resulted in the inhibition of M. haemolytica in our study. Similar to ajowan and thyme, major compounds detected in fennel (anethole), cinnamon leaf (eugenol) and citronella (linalool and geraniol) EOs have been shown to inhibit either Gram‐negative or ‐positive bacteria previously (Lopez et al .…”
Section: Discussionmentioning
confidence: 62%
“…This compound has previously been reported to confer antimicrobial activity against bovine respiratory pathogens (Kissels et al . ), and likely resulted in the inhibition of M. haemolytica in our study. Similar to ajowan and thyme, major compounds detected in fennel (anethole), cinnamon leaf (eugenol) and citronella (linalool and geraniol) EOs have been shown to inhibit either Gram‐negative or ‐positive bacteria previously (Lopez et al .…”
Section: Discussionmentioning
confidence: 62%
“…Animal studies have shown improvement of mucociliary clearance [Wienkötter et al 2007], anti-inflammatory properties [Vigo et al 2004], and antibacterial activity [Stojković et al 2013] in the respiratory system. As shown by Kissels et al [2017], both thymol and carvacrol have an additive effect in combination with tilmicosin against microorganisms isolated from the respiratory tract of calves. A similar effect was observed after administration of a combination of thymol with doxycycline.…”
Section: Potential Use Of Phytobiotics For Treatment and Prophylaxis mentioning
confidence: 93%
“…The major component in the anise EO is trans-anethole (Orav et al, 2008). In an in vitro experiment by Kissels et al (2017), trans-anethole and 1,8-cineole did not show any antibacterial effects whereas a synergistic effect was observed for carvacrol and thymol. Due to the synergistic and additive effects of EO compounds, the overall composition of different EO and a combination thereof may cause complex effects on rumen fermentation and animal metabolism, which makes it difficult to compare the results of studies using mixtures of different EO.…”
Section: Effects Of the Eo Mixture On Intake Milk Yield And Milk Gromentioning
confidence: 94%